Recruitment and Retention Strategies for Gifted Students from Diverse Ethnic, Cultural, and Linguistic Backgrounds: A Multicultural Literature Review from the Perspective of James A. Banks - Alan Alda Nugroho; Samsul Hadi; Asrizal Septi Wibowo; Mazlina Nurmaiza; Elisa Nur Maharani Husna (Civiliza Publishing, Indonesia., 2026)
This study explores the recruitment and retention strategies for gifted students from diverse ethnic, cultural, and linguistic backgrounds, as outlined by Donna Y. Ford in the book Multicultural Education: Issues and Perspectives, edited by James A. Banks and Cherry A. McGee Banks. The objective of this research is to evaluate fair and inclusive approaches in identifying and retaining students from historically underrepresented groups in gifted education programs. Employing a library research method and content analysis, this study reveals three main findings: (1) key recruitment barriers include unequal access to quality education, culturally biased assessment standards, and a lack of multicultural training for educators; (2) recruitment strategies must be systematic, inclusive, and culturally responsive; and (3) retention strategies require the implementation of multicultural education, supportive learning environments, and curriculum development that emphasizes diversity and equity. These findings highlight the necessity of integrated efforts among schools, educators, and policy makers to establish a gifted education system that is equitable and inclusive for all students.